Temporomandibular Joint Ankylosis among Patients at Saint Paul’s Hospital Millennium Medical College, Ethiopia: A 9-Year Retrospective Study - Dereje Mekonnen; Andamlak Gizaw; Bruktawit Kebede (International Journal of Dentistry)
Background. Temporomandibular joint ankylosis (TMJA) is a gradually developing pathological condition manifested by a limited mouth opening. It can result in an extremely disabling deformity that may affect mastication, swallowing, speech, oral hygiene, and facial cosmetic appearance. The present study aimed to determine the pattern of TMJA at St. Paul’s Hospital millennium medical college (SPHMMC), Addis Ababa, Ethiopia. Methods. A retrospective descriptive study design was conducted at SPHMMC. All medical records of patients with the diagnosis of TMJA that visited the Maxillofacial Surgery unit from September 2010 through August 2019 were reviewed. Sociodemographic and clinical data including age, sex, place of residency, duration of TMJA cases, etiology, clinical presentations, imaging results, type of surgical operation, and complications after surgery were collected and analyzed using IBM SPSS software version 20 for Windows (Armonk, NY, USA: IBM Corp) computer program. Results. A total of 130 patients’ medical records were reviewed. Out of this, 95 were included in the study. Forty-two (44.2%) of the TMJA cases were males, while the remaining 53 (55.8%) were females with a male to female ratio of 0.79 : 1. 20–29-year-old patients were the most affected, 36 (37.9%), followed by the 30 to 39 years age group, 33 (34.7%). Trauma (77.9%) was identified as the most common cause of TMJA. Notably, bilateral ankylosis (72.6%) was more common than unilateral (27.3%), and micrognathia was the most common (23.0%) deformity observed. The majority 52 (54.7%) of TMJA patients were treated with gap arthroplasty. Conclusions. TMJA was predominant among females than their male counterparts. Of note, 20–29-year-old patients were the most affected group. The majority of TMJA cases were treated by gap arthroplasty with almost no postoperative complications. Early detection and intervention to release the ankylosed joint is needed to improve patients’ quality of life.